Smart Contract Governance: A Comparative Study of ASEAN (Association of Southeast Asian Nations) Countries - Dikha Anugrah; Sineenat Suasungnern; Fariza binti Romli (Universitas Kuningan, 2026)
The rapid development of blockchain has given rise to smart contracts that challenge traditional legal doctrine, even though the technology is crucial to supporting SDGs (Sustainable Development Goals) 9 and 16. Purpose: This study aims to analyze smart contract governance in Indonesia, Malaysia, and Thailand to support the achievement of the SDGs in the region. Method: A normative-comparative legal method is used with a socio-legal approach. This study examines the synchronization of regulations and the socio-institutional impacts. Results: The validity of smart contracts in the three countries is interpretative due to the lack of specific regulations. The self-executing and immutable nature triggers doctrinal tensions related to agreements and consumer protection, which are increased by the digital literacy gap. Conclusion: Smart contract governance in Southeast Asia requires an adaptive regulatory strategy that balances innovation and legal certainty. Suggestion: Authorities are expected to develop co-regulation-based regulations, strengthen digital institutions, and initiate regional legal standardization across ASEAN (Association of Southeast Nations). Contributions: The contribution is in the development of a blueprint for regional digital law harmonization that integrates aspects of dogmatic law with legal sociology. This study offers a model for ASEAN legal standardization that bridges technological innovation with social justice and provides indicators of institutional readiness replicated by developing countries in embracing an inclusive and sustainable digital economy.